2022
DOI: 10.3389/fpsyg.2022.918128
|View full text |Cite
|
Sign up to set email alerts
|

Faultline configurations affecting the entrepreneurial team performance of new generation of returning migrant workers in China: An empirical study based on fuzzy-set qualitative comparative analysis

Abstract: As the impact of faultlines is still without a consensus, to figure out how faultlines will hurt or promote the entrepreneurial performance can help the new generation of Chinese migrant workers to start their businesses successfully under the Rural Revitalization Strategy. This study addressed a fuzzy-set qualitative comparative analysis (fsQCA) based on 32 returning entrepreneurial teams from a complexity perspective. We firstly introduced three faultline categories for migrant workers and selected five of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…In turn, these different attributes affect the process of strategic decision making and implementation, and eventually affect team outcomes (Hutzschenreuter and Horstkotte, 2013;Li and Jones, 2019;Ma et al, 2021). Studies have shown that TMT faultlines have a significant impact on strategic decisions, such as those made in relation to green technology innovation (Ma et al, 2021), over-investment (Xie et al, 2022), strategic change (Richard et al, 2019;Wu et al, 2021;Zhang et al, 2021), service transition (Chen and Wang, 2021), competitive behavior (Li and Jones, 2019), and entrepreneurial performance (Qiu et al, 2022). In light of the significant explanatory power of TMT faultlines, this paper suggests that linking TMT faultlines and corporate industrial diversification is a worthwhile research endeavor, as the industrial diversification literature in recent years has increasingly focused on the important role of top managers' representations and perceptions (Neely et al, 2020;Elia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, these different attributes affect the process of strategic decision making and implementation, and eventually affect team outcomes (Hutzschenreuter and Horstkotte, 2013;Li and Jones, 2019;Ma et al, 2021). Studies have shown that TMT faultlines have a significant impact on strategic decisions, such as those made in relation to green technology innovation (Ma et al, 2021), over-investment (Xie et al, 2022), strategic change (Richard et al, 2019;Wu et al, 2021;Zhang et al, 2021), service transition (Chen and Wang, 2021), competitive behavior (Li and Jones, 2019), and entrepreneurial performance (Qiu et al, 2022). In light of the significant explanatory power of TMT faultlines, this paper suggests that linking TMT faultlines and corporate industrial diversification is a worthwhile research endeavor, as the industrial diversification literature in recent years has increasingly focused on the important role of top managers' representations and perceptions (Neely et al, 2020;Elia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%